2007
DOI: 10.1097/01.mao.0000265190.29969.12
|View full text |Cite
|
Sign up to set email alerts
|

Valacyclovir and Prednisolone Treatment for Bell's Palsy

Abstract: The valacyclovir and prednisolone therapy was more effective in treating Bell's palsy, excluding zoster sine herpete, than the conventional prednisolone therapy. To our knowledge, this is the first controlled study of an antiviral agent in the treatment of a sufficient number of Bell's palsy cases based on an etiologic background.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(58 citation statements)
references
References 27 publications
(19 reference statements)
2
52
1
1
Order By: Relevance
“…It did not show any benefit of acyclovir, in contrast to a recent randomised trial of valcyclovir and prednisolone that suggested that antiviral treatment is effective 4. However, the results of the latter study need to be interpreted with caution because of several methodological flaws, including lack of assessor blinding and low follow-up rate.…”
contrasting
confidence: 60%
“…It did not show any benefit of acyclovir, in contrast to a recent randomised trial of valcyclovir and prednisolone that suggested that antiviral treatment is effective 4. However, the results of the latter study need to be interpreted with caution because of several methodological flaws, including lack of assessor blinding and low follow-up rate.…”
contrasting
confidence: 60%
“…Among these 39 studies, 1 studies were duplicates, 13 studies were ineligible, leaving 12 studies to review. Six studies were excluded; two were in Spanish, one was in German, and 3 were subsets or duplicated reports, leaving six studies[8-10,12,13,25] with a total of 1805 patients for analysis. Characteristics of the 6 included studies are described in table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Characteristics of the 6 included studies are described in table 1. Five studies[8-10,12,13] compared recovery rates of AVT plus corticosteroid with corticosteroid alone or placebo; the remaining study directly compared the recovery rate of AVT against corticosteroid[25]. Two studies were based on factorial design[9,12] and the others were parallel randomized control trials.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…11 There is currently no evidence to support the use of either antiviral drug on its own, 12,13 and there is uncertainty regarding the benefit of adding them to corticosteroids.…”
Section: Antiviral Drugsmentioning
confidence: 99%